Prestressed Stainless Steel Stayed Columns with Two Crossarms - Machacek, Josef; Pichal, Radek (Advances in Technology Innovation, 2019)
The efficiency of prestressed stayed elements when designing very slender steel columns was proved for both stability and strength capacity of the columns. With an increasing number of crossarms placed along the length of the column the effectiveness is further growing in comparison to a stayed column with just one crossarm. First the stability of an “ideal” (perfect) prestressed stayed column with two crossarms is investigated analytically. Similar principal behavior as in the case of prestressed stayed columns with just one crossarm is confirmed and the three zones depending on the value of prestressing are revealed. Expressions for minimal, optimal and maximal prestress are derived analytically. After receiving critical buckling value of the stayed column with the two crossarms without any prestressing by linear buckling analysis (LBA), the maximal critical buckling loading of the column under optimal prestressing is derived. The results are fully demonstrated on a practical example. Second the strength capacity of such column but with relevant initial deflections is investigated by the geometrically and materially nonlinear analysis with imperfections (GMNIA) using ANSYS software. Comparisons of critical and strength values under various prestressing are analyzed with respect to a practical design. Finally some recommendations for following studies and practical use are given.